(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper the origin of two Ibero-Romance terms for skin diseases, namely sarna and caspa, is carefully discussed. The Indo- European data strongly suggest that both these words were borrowed from a Indoeuropean substatum (vel IE substrata), which existed in the Hispanica Peninsula before the Roman conquest. It seems plausible to conclude that these items are of Celtic origin.